Division VII: The Galactic System - Gerhard, Ortwin; Hatzidimitriou, Despina; Whitelock, Patricia A.; Lada, Charles J.; Sarajedini, Ata; Wyse, Rosemary F.; Lazio, Joseph (2009)
Division VII gathers astronomers studying the diffuse matter in space between stars, ranging from primordial intergalactic clouds, via dust and neutral and ionized gas in galaxies, to the densest molecular clouds and the processes by which stars are formed.